Technological Diversification In The Promotion And Counter-Propaganda Of Spiritual And Educational Work (Texas Journal of Multidisciplinary Studies, 2022)
Explains the technological approach to the implementation of propaganda and counterpropaganda work among young people and the extent to which it has a positive impact on the minds of young people and the essence of the ongoing process of renewal in Uzbekistan; formation of devotion to our national customs and traditions; formation of social skills and competencies for high spirituality and enlightenment; teaching creativity, free and independent thinking; respect for the elderly, respect for the young, and the promotion of a culture of community control in the neighborhood